Lie Conformal Algebras of Planar Galilean Type. Issue 2 (April 2018) - Han, Xiu; Wang, Dengyin; Xia, Chunguang
Abstract : Motivated by the Lie structure of the planar Galilean conformal algebra, we construct a class of infinite rank Lie conformal algebras C P G ( a, b ), where a, b are complex numbers. All their conformal derivations are shown to be inner. The rank-one conformal modules and ℤ-graded free intermediate series modules over C P G ( a, b ) are completely classified. The parallel results of the finite Lie conformal subalgebra C P G ( a, b ) of C P G ( a, b ) are also presented.